Комплексна навчально-виховна парадигма як засіб реформування будівельної галузі в сучасному світі : принципи , модель, рішення - Тимофєєв, Ю. Е.; Нікогосян, Н. І.; Євдоченко, О. М. (Ways to Improve Construction Efficiency, 2013)
In article consider and explorer new conception to reform of construction. Fundamental item of that concept is deep and circumstance changes to preparation of personnel for branch. The concept be based on of many years experience of author as educationist and manager of Service of volunteering, socialing and favour of KNUCA.